Pengaruh Penambahan Palm Oil Fuel Ash terhadap Nilai Kuat Tekan Bebas Tanah berdasarkan Hasil Uji UCT - Ningrum, Puspa; Toyeb, Muhammad; Auliandi, Muhamad (Sekolah Tinggi Teknologi Pekanbaru, 2023)
In general, problematic soil needs to be repaired so that the basic soil becomes better and can be requirements for a construction base. In this research, an alternative soil stabilization was carried out by adding Palm Oil Fuel Ash (POFA). POFA has pozzolanic properties which are very useful in the soil stabilization process because it can increase the binding force between stabilized soil particles. In this research, POFA was used as a mixture in basic soil with percentages of 20%, 30%, and 40%. The age of curing was carried out for 0, 7, 14, and 28 days. Based on the research results, it was found that adding POFA was effective for increasing soil strength, namely at percentages of 20%. If the percentage content of POFA is too much, the binder contained in the mixed soil can affect the behavior of the soil when it reacts with water. By increasing the POFA content by 20%, the maximum plasticity index (PI) decrease was obtained, namely 8.52% and the maximum unconfined compressive strength value was 240.82 kN/m2 at a curing age of 28 days.